Antiferromagnetic Ising model with frustration on Graphenylene lattice - Yoshida, M. [UNESP]; Paupitz, R. [UNESP] (Elsevier, 2023)
Frustration effects due to competition between nearest-neighbor and next-nearest-neighbor spins interaction on the graphenylene lattice, also known as biphenylene carbon lattice, were investigated by Monte Carlo simulations. We identified two possible phases from our results of the entropy at zero temperature, namely an ordered spin glass and other an antiferromagnetic phase. Despite the complexity of the lattice, a finite size scaling analysis for the antiferromagnetic regime shows that it can be classified into the same universality class of the usual Ising model. The canonical probability distribution as a function of the spin glass order parameter was computed and the continuous spin glass phase transition confirmed.
Keywords: 2-D materials; Antiferromagnetism; Frustration; Graphenylene; Ising model; Spin glass